Factors of Loss to Follow-up Antiretroviral Therapy in Islanded Area (Unnes Journal of Public Health, 2018)
ABSTRACT Loss to follow-up of antiretroviral therapy is when PLWHA (People Living with HIV/AIDS) do not come for antiretroviral therapy for more than 3 months. This study aimed to determine the factors of loss to follow-up antiretroviral therapy for PLWHA at Prof. Dr. W. Z. Johannes Kupang Public Hospital where PLWHA with land, water and air transportation are served. This was a case control study with 66 samples of PLWHA. The samples underwent antiretroviral therapy in Prof. Dr.W.Z. Johannes Kupang Public Hospital from 2006 to 2016. Saturated sampling technique was done for cases group and simple random sampling was done for control group. Univariate and bivariate data analysis were done in this study. The result of bivariate analysis showed that there were association between intention (p = 0.004, OR = 4.667), self efficacy (p = 0.0001, OR = 7.875), action (p = 0.0001, OR = 45.000), transportation mode (p = 0.046, OR = 0.200), and transport costs (p = 0.0001, OR 19.333) and loss to follow-up antiretroviral therapy. It could be concluded that transportation and behavior were the major problems for the loss to follow up antiretroviral therapy in the islanded area. Keywords: HIV/AIDS, antiretroviral therapy, loss to follow-up, islanded area ABSTRAK Gagal follow-up antiretroviral therapy adalah jika ODHA (Orang dengan HIV/AIDS) tidak menjalani terapi antireroviral lebih dari 3 bulan terakhir. Penelitian ini bertujuan untuk mengetahui faktor-faktor gagal follow-up antiretroviral therapy pada ODHA di RSUD Prof. Dr. W. Z. Johannes Kupang yang melayani para ODHA dengan moda transportasi darat, air, dan udara. Desain penelitian ini adalah case control. Sampel sebanyak 66 ODHA yang menjalani antiretroviral therapy di RSUD Prof. Dr.W.Z. Johannes Kupang sejak tahun 2006 sampai 2016. Teknik pengambilan sampel yang digunakan adalah sampel jenuh untuk kelompok kasus dan simple random sampling untuk kelompok kontrol. Analisis data menggunakan prosentase untuk univariat dan bivariat. Hasil analisis bivariat menunjukkan ada pengaruh niat (p = 0,004, OR = 4,667), self efficacy (p = 0,0001, OR = 7,875), tindakan (p = 0,0001, OR = 45,000), moda transportasi (p = 0,046, OR = 0,200), dan biaya transportasi (p = 0,0001, OR 19,333) terhadap gagal follow up terapi antiretroviral. Dapat disimpulkan bahwa masalah utama gagal follow up terapi antiretroviral di wilayah berkepulauan ini adalah transportasi dan perilaku. Kata Kunci: HIV/AIDS, terapi antiretroviral, gagal follow up, wilayah berkepulauan.